Evolution of visceral leishmaniasis in São Luís, Maranhão: an epidemiological and temporal analysis of cases (Research, Society and Development, 2020)
Visceral Leishmaniasis (VL), popularly known as kala-azar, dundun fever or tropical splenomegaly, is a zoonosis that affects humans and other domestic and wild animal species. The present work aims to carry out an epidemiological analysis from 2008 to 2017 of visceral leishmaniasis in the city of São Luís–MA. A retrospective, descriptive and quantitative study was carried out on the confirmed cases of visceral leishmaniasis reported in the municipality of São Luís, capital of Maranhão state, between 2008 and 2017. All information was collected during March 2019. using as source the Information System for Notification of Disorders (SINAN), database provided by the Department of Informatics of the Unified Health System (DATASUS). The Reporting Disease Information System (SINAN) recorded 37,639 cases of visceral leishmaniasis in Brazil between 2008 and 2017. About half of this amount corresponds to the northeast region, which had 19,841 (52.71%) confirmed cases during this period. We can see that most of the confirmed cases of visceral leishmaniasis in the city of São Luís between 2008 and 2017 show that it was male with 1,094 (64.28%), especially individuals of race / brown color, and children with between 01 and 04 years old, with incomplete elementary school education from 1st to 4th grade. After concluding that most people are infected in the urban area, there is a need for a broader health system so that patients do not approach treatment because it is critical that therapy be performed until the final healing process.